Influence of cage farming on feeding and reproductive aspects of Pimelodus maculatus Lacépède, 1803 (Siluriformes: Pimelodidae) in the Chavantes reservoir, Brazil - doi: 10.4025/actascibiolsci.v36i1. - Heleno Brandão; Julio Cesar de Oliveira Santana; Igor Paiva Ramos; Edmir Daniel Carvalho (Acta Scientiarum. Biological Sciences, 2013)
This study evaluated the diet and reproductive aspects of the population of Pimelodus maculatus around net cage fish farming in order to assess the possible impacts of this activity. Monthly collections were performed from March 2008 to February 2009 on two populations: one close to the net cages (NC) and one from an area not influenced by these cages denominated the “reference site” (RS). Results of the Alimentary Index (AI), Gonadosomatic Index (GSI), reproductive potential and histological analysis were obtained for both NC and RS populations. The population from NC used leftover food (ration) that escapes from net cages as the main food item (99.3%). For the RS population, the detritus item was the more important food source (51.7%). The Detrended Correspondence Analysis (DCA) showed that the use of food resources was different between the two sites. The reproductive period of the species (indicated by the GSI) revealed that the population of the NC showed an extended reproductive period compared to RS. The histology of the ovaries indicated that the specimens in the NC were spawning capable. This study indicates that fish farming activities influence the species P. maculatus in the Chavantes reservoir by adding a new resource to the food web.